PENGARUH BUERGER ALLEN EXERCISE TERHADAP NILAI ANKLE BRACHIAL INDEX PADA PASIEN DIABETES MELITUS - Pratiwi Christa Simarmata; Sari Desi Esta Ulina Sitepu; Abdi Lestari Sitepu; Ruttama Hutauruk; Rita Ayu Butar-butar (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Diabetes mellitus is a disorder of the endocrine system characterized by increased levels of glucose in the blood. The purpose of this study was to assess the effect of Buerger's Allen exercise on the value of the ankle brachial index (ABI) in patients with diabetes mellitus. The research design was a quasi-experimental pretest and posttest without a control. The study was conducted from March to May 2021 at Grandmed Lubuk Pakam Hospital with 48 respondents, with consecutive sampling technique. Data were analyzed using the Wilcoxon test. The Buergers Allen exercise intervention was performed twice a day, for three weeks. The procedure is performed by lifting the lower extremities up at an angle of 45-90 degrees for 2-3 minutes, then the patient sits at the bedside with the legs hanging down, accompanied by flexion, extension, pronation and supination movements for 5-10 minutes, and the patient lies down. with both feet resting for 10 minutes. There was a significant effect between the mean ABI value before intervention 0.83 and after intervention 0.95, p=0.00. The difference in mean ABI p=0.000, p<0.05. The results of the study concluded that there was an effect of buerger allen exercise on the ABI value before and after the intervention where the ABI value was getting better. It is recommended for nurses to make Buergers Allen exercise one of the independent nursing interventions in providing nursing care to patients with diabetes mellitus.